Cost estimation of micro-hydropower equipment in Nepal. (2022) - Butchers, Joe; Williamson, Sam; Booker, Julian; Maitland, Topaz; Karki, Prem Bikram; Pradhan, Bikram Raj; Pradhan, Suman Raj; Gautam, Biraj
Abstract: Selecting the appropriate technology for providing electricity to rural communities depends upon evaluating the cost of a potential installation. For some rural communities, locally manufactured technology, in the form of wind and hydropower, can be effective. However, often the cost of these locally manufactured technologies is largely unknown. Access to costing data allows the economic viability of a site to be compared with other options. Furthermore, it enables benchmarking, allowing the expected total cost of an installation, or individual sub-systems, to be compared with quotations. This paper attempts to address the current lack of publicly available costing information for locally manufactured micro-hydropower equipment. A methodology is presented where quotations are provided by micro-hydropower manufacturing companies in Nepal for randomly generated sites. Using that information, they provided a quotation for various sub-systems. This data allows comparison of the cost of major components and the influence of turbine type. Through a linear regression model, expression have been developed that can be used to determine the expected cost for both Pelton and Crossflow turbine installations. The accuracy of these expressions is compared with previous costing models, the outcomes of the work and their significance in the context of Nepal and elsewhere is discussed. The key contribution of this work is establishing numerical expressions which allow proposed costs of micro-hydropower equipment to be rapidly evaluated.